Masalah Pemahaman Mendengarkan Yang Dihadapi Oleh Mahasiswa Semester III Program Studi Pendidikan Bahasa Inggris - Fransiskus Jemadi; Bergita Verlin; Maria Olga Jelimun (Unika Santu Paulus Ruteng, 2023)
The purpose of this research was to investigate students’ listening comprehension problems. The researchers used a mixed-method design. The participants were third-semester students of the English Language Education Program at Universitas Katolik Indonesia Santu Paulus Ruteng. In collecting the data, the researchers used two instruments namely survey questionnaires, and semi-structured interviews. The findings of this study revealed that the third-semester students of the English Language Education Study Program perceived some degree of listening comprehension problems. Parsing problems took 50%, utilization problems took 30%, and perception problems took 20% of listening comprehension problems faced by the third-semester students. In addition, the results of the interview revealed that mostly the students experienced listening comprehension problems due to the fast speech rate of the speakers in the recording. Another cause of their listening comprehension was the lack of vocabulary and unfamiliar topics which made them unable to comprehend the spoken texts. In conclusion, the listening difficulties encountered by the third-semester students were to due the semantics and lexical meaning of the spoken text